Study on water quality index of the Sungai Soi, Kuantan, Pahang - Mohd Azizi, Abdul Manap (2014)
The Sungai Soi, Kuantan, Pahang has been selected to study of the water quality for its importance and function to the communities. The local peoples are using this river as a source of water. Due to the rapid development and urbanization process around the study area, the water quality of the Sungai Soi is significantly disturbed and the possibility of pollution. A total of twelve water quality parameters were analyzed including in situ test and laboratory analysis. Water samples were assessed by analyzing the various physic-chemical parameter such as pH value, turbidity, electrical conductivity (EC), dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), ammonia nitrogen (NH 3 -N), nitrate (NO3), phosphate (PO4), sulphate (SO4),total suspended solids (TSS) and total dissolve solid (TDS). A total of 6 parameters were considered to calculate the Water Quality Index (WQJ). According to the result, it was found that the Sungai Soi is in class 4 which is suitable for irrigation purpose only and not suitable for drinking or recreational purpose. It also can be conclude that water quality index can play a big role in ascertain quality of river during various season and location. The result revealed that the study areas were slightly polluted to polluted due to anthropogenic activities such as agriculture activities. It was also found that most of the parameter reading for all station was higher during the wet day due to the surface runoff and urban storm-water' runoff.